2021
DOI: 10.1021/acsaem.1c03080
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Methanol to Formaldehyde and Hydrogen on Pd/TiO2 by Photocatalysis in Direct Sunlight: Structure Dependent Activity of Nano-Pd and Atomic Pt-Coated Counterparts

Abstract: In the present investigation, facet-controlled Pd nanoparticles with nanocube (PdNC) and truncated octahedron (PdTO) morphologies, and their counterparts with half-a-monolayer of atomic Pt coated (0.5θPt-PdNC and 0.5θPt-PdTO) surfaces were prepared. All of them were characterized and evaluated as cocatalyst after supporting them on commercial titania (P25) (PdNC/P25, PdTO/P25, 0.5θPt-PdNC/P25, and 0.5θPt-PdTO/P25) under direct sunlight and/or one sun conditions for the oxidation of methanol to formaldehyde alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…This observation underscores that Ptcoating on Pd enhances hydrogen generation; it is also notable that irrespective of catalysts, thin film form shows higher H 2 production than powder form and these results are consistent with our earlier reports. [21,31,33] While light scattering decreases the effective light absorption in the suspension form, efficient light absorption and internal light scattering within the thin film form enhance the rate of reaction in thin film form; [22] efficient light absorption in turn promotes more charge carriers generation and thus improves the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation underscores that Ptcoating on Pd enhances hydrogen generation; it is also notable that irrespective of catalysts, thin film form shows higher H 2 production than powder form and these results are consistent with our earlier reports. [21,31,33] While light scattering decreases the effective light absorption in the suspension form, efficient light absorption and internal light scattering within the thin film form enhance the rate of reaction in thin film form; [22] efficient light absorption in turn promotes more charge carriers generation and thus improves the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed procedure is given in our earlier publication. [21] As prepared Pd-nanoparticles is further cleaned with NaBH 4 to remove any absorbed impurities, such as PVP, before Pt-coating. 60 mg NaBH 4 in 5 ml water was mixed with 5 ml of nanoparticle solution and heated to 85 °C and kept at the same temperature for 3 h under constant stirring.…”
Section: Synthesis Of Pd Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Nalajala et al [95] report on the production of a costeffective photocatalyst and its performance under (artificial and real) sunlight to produce CH 2 O and H 2 from CH 3 OH. As Pt has excellent H 2 adsorption/desorption characteristics, but is more expensive than other cocatalysts, they coated only half a monolayer of Pt on Pd nanoparticles supported on TiO 2 and achieved enhanced activity.…”
Section: Photocatalytic Ch 3 Oh Conversion To Ch 2 Omentioning
confidence: 99%
“…Delightfully, recent studies indicated that dehydrogenation of methanol to formaldehyde could also be achieved in heterogeneous photocatalytic systems under mild conditions. 27 These heterogeneous photocatalysts could be easily isolated and reused compared with homogeneous catalysts. 28 Moreover, the photoexcited electrons and holes (charge carriers) could bypass the external redox reagent to complete the chemical conversion.…”
Section: Introductionmentioning
confidence: 99%